Social competence, personality and adult attachment style in a Portuguese sample - Moreira J.; Bernardes, S.F.; Andrez M.; Aguiar P.; Moleiro, C.; Silva M. F. (Personality and Individual Differences, 1998)
The aim of the present study was to examine the correlates of adult attachment style, measured using a Portuguese translation of the paragraphs proposed by Hazan and Shaver (1987). University students (N = 138) responded to this measure. to the Social Competence Questionnaire(ComQ) and to the Eysenck Personality Inventory (EPI). Percentages found for each attachment style were similar to those found by other authors. Secure participants scored higher in social competence. In the EPI, the anxious/ambivalent group was higher in neuroticism, whereas the avoidants leaned toward introversion. Differences in correlations among social competence and personality scales were also found in different attachment styles.